The Effect of Virechana with Manibhadra Churna in Psoriasis - A Case Study (Global Journal of Medical Research, 2021)
Panchakarma is referred as penta-biopurificatory process. Virechana Karma is one among Panchakarma; by which orally administered drug acts on internal Dosha especially Pitta Dosha and expel them out of the body through Guda. Psoriasis is a common chronic skin disorder of autoimmune origin. A 42 year old male patient c/o itching overhead, behind the ears, nails, lower back and legs since 2 years and while itching he gets whitish powder. He has consulted a dermatologist and has taken modern medicine. He got symptomatic relief. As soon as he stops medicines, the condition worsens and reoccurrence of disease was going on. Meanwhile severe burning sensation on chest was also happened. So he has planned to take Ayurveda treatment for the same. There was no history of any systemic illness. The present case was diagnosed as psoriasis from a detailed history taking and clinical examination. A positive family history was noted. A classical way of Virechana Karma was planned with Manibhadra Churna. After Virechana, Samyaka Shudhi Lakshana was achieved; symptoms such as itching, erythema, scaling, candle grease sign and Auspitz sign were not found. Reoccurrence of disease was not found even after 2nd follow up.
Keywords: virechana; psoriasis; manibhadra churna; kushta.